2006
DOI: 10.1016/j.csda.2004.11.009
|View full text |Cite
|
Sign up to set email alerts
|

Nearest neighbours in least-squares data imputation algorithms with different missing patterns

Abstract: Birkbeck ePrints: an open access repository of the research output of Birkbeck College http://eprints.bbk.ac.uk Wasito, I. and Mirkin, B. (2006). Nearest neighbours in least-squares data imputation algorithms with different missing patterns. Computational Statistics & Data Analysis 50 (4) 926-949.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 18 publications
0
14
0
Order By: Relevance
“…Finally, Table 1 shows the imputation results of the missing values of mass. To evaluate the performance of the proposed imputation method, comparison is made between the proposed method and the mean imputation method in terms of the squared imputation error (IE) (see [22]). …”
Section: Imputation Resultsmentioning
confidence: 99%
“…Finally, Table 1 shows the imputation results of the missing values of mass. To evaluate the performance of the proposed imputation method, comparison is made between the proposed method and the mean imputation method in terms of the squared imputation error (IE) (see [22]). …”
Section: Imputation Resultsmentioning
confidence: 99%
“…The NIPALS algorithm was applied to the NSW Ambulance dataset and the obtained PCA model is used to predict the missing values. (40) Of the total number of items on the SF-36 survey (26,982) a total of 538 (1.9%) were not answered and therefore imputed.…”
Section: Discussionmentioning
confidence: 99%
“…It is easy to show that Cov (0) The structure of eigenvalues of Cov(0) has been investigated by Wasito and Mirkin (2006) who found that, of q nonzero eigenvalues, the maximal one is λ=1+(M-q)q whereas all the other q-1 eigen-values are equal to unity. This provides for really elongated shapes, so that we could check whether this change of the shape indeed affects the clustering results.…”
Section: Data and Cluster Structure Parametersmentioning
confidence: 99%